Influência da profundidade e dos parâmetros ambientais sobre o desenvolvimento de Gracilaria birdiae (Rhodophyta, Gracilariales) em viveiro de camarão - Oliveira, Vinícius Peruzzi de (2007)
This study evaluates the influence of depth and environmental parameters on the development of Gracilaria birdiae Plastino & Oliveira (Gracilariaceae Rhodophyta) in an organic shrimp pound (Litopenaeus vannamei) under euthrophical conditions. PVC structures (module) witch four ropes laden with 150 g of macroalgae each, were kept during 35 days at three different depths (surface, 10 and 20 cm depth). Wet biomass weighing and environmental parameters (temperature, salinity, turbidity, pH, transparence, precipitation, evaporation, insolation, accumulated solar radiation, nitrite, nitrate, ammonium and orthophosphate) were measured weekly. At all three proposed depths, the macroalgae displayed a higher biomass at the end of experiment than at the initial inoculations. The module kept at a 10 cm depth presented the greatest average biomass (186,3), followed by that kept at 20 cm (180,4 g) and the surface module (169,9 g). Biomass variations showed algae to suffer the direct effects of depths. Biomass loss was associated with the factors that influence light penetration, such as sediment deposits above the thallus, rate of evaporation and precipitation. The smallest loses occurred in the algae kept on surface (0,16%), followed by the algae kept at 20 cm (0,20%) and 10 cm (0,22%). The specific growth rate (SGR) of G. birdiae showed no significant difference between the three depths nor the sample periods. Nevertheless, the modules kept at 10 and 20 cm depths presented similar growth evolution, both growing 0,38%·per day-1, while the module kept on surface had an average SGR of 0,36%·day-1. The models related to growth rate demonstrated temperature, salinity, pH, orthophosphate, ammonium, precipitation and turbidity as the principal environmental parameters influencing the development of G. birdiae